2000
DOI: 10.1530/eje.0.1430657
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, computed tomography and fat cell data in an obese population: relationship with insulin, leptin, tumor necrosis factor-alpha, sex hormone-binding globulin and sex hormones

Abstract: Objective: To correlate anthropometric, computed tomography and fat cell data from abdominal regions with the levels of serum insulin, C-peptide, leptin, tumor necrosis factor-alpha (TNF-a), testosterone, 17b-estradiol, androstenedione, dehydroepiandrosterone sulphate (DHEA-S) and sex hormone-binding globulin (SHBG). Design and methods: The sample consisted of 84 obese patients (29 men, 22 premenopausal women and 33 postmenopausal women) who had undergone abdominal surgery. Weight, height, percentage of body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
154
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 40 publications
(36 reference statements)
10
154
2
4
Order By: Relevance
“…Like leptin [28,29], the CD40 mRNA level was 45% higher in SAT than in VAT. This could be due to larger fat cells in SAT than VAT [30], in line with the notion that leptin production is correlated with the degree of adipocyte development [31]. Overall these data showed that CD40 expression by the adipocyte is mainly restricted to the late stage of adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…Like leptin [28,29], the CD40 mRNA level was 45% higher in SAT than in VAT. This could be due to larger fat cells in SAT than VAT [30], in line with the notion that leptin production is correlated with the degree of adipocyte development [31]. Overall these data showed that CD40 expression by the adipocyte is mainly restricted to the late stage of adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies found a lower diastolic blood pressure in the supine position as compared to the sitting position [42,43]. The waist circumference at the level of umbilicus was smaller than that at the midpoint between the lower border of the rib cage and the iliac crest [44] and the BMI was also significantly greater among GDM and SP subjects than among the general population subjects in this study. Moreover, glucose results measured by the Yellow Springs glucose analyser on plasma or serum samples were lower than results from other glucose oxidase methods [45].…”
Section: Discussionsupporting
confidence: 43%
“…Waist circumference has been described as the best anthropometric index for estimation of visceral fat content. 29,30 Indeed, in the clinical practice, metabolic syndrome is diagnosed in men with a waist perimeter higher than 94 cm plus any two of the following parameters: high serum triglycerides, low HDL cholesterol concentrations, high serum glucose and high blood pressure. 19 Taking this definition into account, the patients studied in the present work suffered from metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%